Hippocalcin‐like 1 suppresses hepatocellular carcinoma progression by promoting p21Waf/Cip1 stabilization by activating the ERK1/2‐MAPK pathway. Issue 3 (3rd February 2016) - Zhang, Yonglong; Liu, Yanfeng; Duan, Jinlin; Yan, Haibo; Zhang, Jun; Zhang, Huilu; Fan, Qi; Luo, Feifei; Yan, Guoquan; Qiao, Ke; Liu, Jie
Abstract : Hepatocellular carcinoma (HCC) is the third leading cause of cancer‐related death. However, the underlying mechanism during hepatocarcinogenesis remains unclarified. Stable isotope labeling by amino acids in cell culture (SILAC) is a powerful quantitative strategy for proteome‐wide discovery of novel biomarkers in cancers. Hippocalcin‐like 1 (HPCAL1) is a calcium sensor protein. However, the biological function of HPCAL1 is poorly understood in cancers, including HCC. Herein, HPCAL1 was identified by SILAC as a novel hepatocarcinogenesis suppressor down‐regulated in HCC cell lines and tissues. Importantly, lost expression of HPCAL1 was associated with worse prognosis of HCC patients. Interestingly, secreted HPCAL1 protein in the plasma dropped dramatically in HCC patients compared with healthy donors. Receiver operating characteristic curve analysis showed that serum HPCAL1 at a concentration of 8.654 ng/mL could better predict HCC. Furthermore, ectopic expression of HPCAL1 suppresses cell proliferation, while depletion of HPCAL1 led to increased cell growth both in vitro and in vivo . Mechanistically, HPCAL1 directly interacted with p21 Waf/Cip1 in the nucleus, which requires the EF‐hand 4 motif of HPCAL1 and the Cy1 domain of p21. This interaction stabilized p21 Waf/Cip1 in an extracellular signal‐regulated kinase 1/2‐mitogen‐activated protein kinase‐dependent manner, which subsequently prevented p21 Waf/Cip1 proteasomal degradation by disrupting SCF Skp2 and CRL4 Cdt2 E3 ligase complexes, resulting in increased protein stability and inhibitory effect of p21 Waf/Cip1 . Notably, the tumor suppressive function of HPCAL1 was dependent on p21 in vitro and in vivo . Consistent with this observation, expression of HPCAL1 and p21 Waf/Cip1 was positively correlated in HCC tissues. Conclusion: These findings highlight a novel tumor suppressor upstream of p21 Waf/Cip1 in attenuating cell cycle progression and provide a promising diagnostic and prognostic factor, as well as a potential therapeutic target for HCC. (Hepatology 2016;63:880–897)